THE FREQUENCY AND DISTRIBUTION OF HUMAN PAPILLOMAVIRUS TYPES IN THE MALE POPULATION - Crnogorac, Maja (Medicinski podmladak, 2025)
Introduction: One of the leading causes of sexually transmitted infections is human papillomavirus (HPV). Depending on the population, the anatomical location of sampling, and the techniques utilized for detection and typing, genital HPV infections can be identified in 16% to 69% of cases in healthy men. The Aim: This research aimed to determine the frequency and distribution of HPV types in the genital tract of men using molecular methods in four cities in the Republic of Serbia. Material and methods: This retrospective study included 468 men with suspected genital HPV infection from Belgrade, Kragujevac, Niš, and Novi Sad. The data were collected in the period from 2017 to 2021. Detection and genotyping of the virus was done using the Real-Time PCR method and Sanger DNA sequencing. Descriptive statistics and the χ2 test were used in the statistical significance testing. Results: The presence of HPV was proven in 77 out of 468 samples (16%). The highest HPV prevalence of 35.2% was detected in men older than 45 years of age. The percentage of positive samples was highest in men from Niš (24%), followed by Kragujevac (22.1%), Belgrade (20%), and Novi Sad (11.6%). The difference in HPV positivity in men between cities was found to be statistically significant (p=0.02). A total of 16 different HPV types were detected. HPV 16 is the most frequently detected genotype (30%), followed by HPV 31 (14%), HPV 52 (14%), while types 56, 11, 33, 39 and 45 were identified with lower frequency. HPV 16 was the most often found type in all cities, except for Kragujevac, where HPV 52, 56, and 59 were the most frequently identified. Conclusion: The results show the presence of 16 different genital HPV genotypes in men with the highest frequency of HPV 16. HPV infection was detected in 16% of cases, where the highest prevalence was observed in older men.